2013
DOI: 10.1007/s11999-013-3073-9
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors for Pulmonary Embolism After Primary Musculoskeletal Tumor Surgery

Abstract: Background Limited information is available regarding the incidence, risk factors, and optimal prophylaxis in orthopaedic oncology patients, although malignancy and major orthopaedic surgery are associated with an increased pulmonary embolism (PE) risk. Questions/purposes We aimed to investigate the incidence of PE after musculoskeletal tumor surgery in Japanese patients and analyze the potential risk factors for PE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Both active malignancy and major surgical procedures are independent risk factors for the development of VTE. Previous studies have found that postoperative thromboembolic complications span all surgical specialties, 3 with high rates following major musculoskeletal surgery 4–7 . This increases morbidity and mortality for patients undergoing these types of procedures 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Both active malignancy and major surgical procedures are independent risk factors for the development of VTE. Previous studies have found that postoperative thromboembolic complications span all surgical specialties, 3 with high rates following major musculoskeletal surgery 4–7 . This increases morbidity and mortality for patients undergoing these types of procedures 8 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the study team persevered and identifi ed that potentially primary malignant bone tumours were associated with higher risk than soft-tissue sarcomas (OR 5.58). Bone tumour resection (OR 7.94) and prosthetic reconstruction (OR 9.15) were associated with a signifi cantly higher risk of PE than soft-tissue tumour resection 4. This study raises more questions than it answers as the authors (and indeedthe readership) are likely to be fl abbergasted by the low incidence of PE in this group.…”
mentioning
confidence: 86%
“…The Diagnosis Procedure Combination database is a national administrative claims and discharge abstract data on acute-care inpatients in Japan, the details of which have been described [6,8,13,14]. Data were collected during 6 months (from July 1 to December 31) until 2010 and throughout the year from 2011.…”
Section: Data Sourcementioning
confidence: 99%